Effects Of Prenatal Gentle Yoga And Dzikir Teraphy On Anxiety Level Of Pregnant Women At Bajeng Public Health Center - Nurhidayah; Hasnah; Jumriani (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2022)
It is estimated that anxiety during pregnancy will affect 15-20% pregnant women and increase the negative risks on pregnant women and their newborn. It is estimated that the prevalence of anxiety of pregnant women is around 7-20% in deceloped countries, while in developing countries, a report states that it is 20% or more. In Indonesia alone, it is reported that 28.7% pregnant women underwent anxiety. Prenatal gentle yoga and dzikir teraphy are nonpharmalogical treatments for resolving anxiety issue. This research aims to figure out the effects of prenatal gentle yoga and dzikir teraphy on anxiety level of pregnant women at Bajeng public health center, Gowa Regency. The research is quantitative. The research design used is pre-experimental deaign with one group pretest and post-test design, involving 1 group. It used intervention of prenatal gentle yoga and dzikir teraphy to decrease anxiety in pregnant woman. The data analysis used is univariate and bivariate analysis. Univariate analysis is used to observe the sample characteristics such as age, education, parity, and gestational age. Bivariate analysis is done to observe the effects of prenatal gentle yoga and dzikir teraphy. The testing used SPSS version 24. The data is normally distributed, thus using paired T-test to figure out the differences of anxiety level on pregnant women. It shows significant results with p-value = 0.000 (the significance level < 0.05). The p-value is less than 0.005, therefore, Ho is denied and Ha is accepted. It is concluded that prenatal yoga and dzikir teraphy were highly effective for reducing the anxiety level on pregnant women at Bajeng Public Health Center, Gowa Regency.